Antifungal Therapy for Systemic Mycosis and the Nanobiotechnology Era: Improving Efficacy, Biodistribution and Toxicity - Souza, Ana C. O.; Amaral, Andre C. (Frontiers in Microbiology, 2017)
Fungal diseases have been emerging as an important public health problem worldwide with the increase in host predisposition factors due to immunological dysregulations, immunosuppressive and/or anticancer therapy. Antifungal therapy for systemic mycosis is limited, most of times expensive and causes important toxic effects. Nanotechnology has become an interesting strategy to improve efficacy of traditional antifungal drugs, which allows lower toxicity, better biodistribution and drug targeting, with promising results in vitro and in vivo. In this review, we provide a discussion about conventional antifungal and nanoantifungal therapies for systemic mycosis.